Requirements for Identification of Low Dose and Non-Linear Mutagenic Responses to Ionising Radiation - Pamela J. Sykes; Tanya K. Day (SAGE Publishing, 2007)
Cancer results from multiple changes in gene expression that can occur both genetically and epigenetically. High doses of radiation can lead to mutations and cancer. At high doses the number of mutations caused by radiation is essentially linear with dose. Low dose radiation induced protective responses observed for cancer in vivo and cellular transformation in vitro would predict that hormetic responses would also be observed in mutation assays. Although there are a large number of different mutation assays available, very few are able to detect changes in mutation frequency in response to very low doses of DNA damaging agents. The easiest way to cope with this lack of data in the low dose range is to invoke a linear-no-threshold model for risk assessment. The reasons for the lack of data are discussed. In order to identify hormetic mutation responses, assays need to have a spontaneous frequency that is high enough to enable a reduction below spontaneous frequency to be detected in a feasible number of scored cells and also need to be able to identify both genetic and epigenetic changes. The pKZ1 chromosomal inversion assay fits the criteria for detecting hormetic responses to low dose radiation.